2014
DOI: 10.1016/j.cell.2014.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Circadian Nuclear Receptor REV-ERBα on Midbrain Dopamine Production and Mood Regulation

Abstract: The circadian nature of mood and its dysfunction in affective disorders is well recognized, but the underlying molecular mechanisms are still unclear. Here, we show that the circadian nuclear receptor REV-ERBα, which is associated with bipolar disorder, impacts midbrain dopamine production and mood-related behavior in mice. Genetic deletion of the Rev-erbα gene or pharmacological inhibition of REV-ERBα activity in the ventral midbrain induced mania-like behavior in association with a central hyperdopaminergic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
288
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(299 citation statements)
references
References 52 publications
10
288
1
Order By: Relevance
“…1K, TH protein levels are higher at subjective dawn (circadian time 00, CT00) than at subjective dusk (CT12) in both of Fig. S2), consistent with the study by other investigators (23). We next cloned a mutant TH promoter that lacks Rev-Erbα binding site and investigated the effect of AHI1 on its activity (Fig.…”
Section: Decreased Th Expression In Ahi1 Ko Mouse Midbrains and Ahi1 supporting
confidence: 68%
See 3 more Smart Citations
“…1K, TH protein levels are higher at subjective dawn (circadian time 00, CT00) than at subjective dusk (CT12) in both of Fig. S2), consistent with the study by other investigators (23). We next cloned a mutant TH promoter that lacks Rev-Erbα binding site and investigated the effect of AHI1 on its activity (Fig.…”
Section: Decreased Th Expression In Ahi1 Ko Mouse Midbrains and Ahi1 supporting
confidence: 68%
“…Many studies indicated that expression of TH is a time-of-day circadian oscillating pattern and its expression is lowered at daytime and raised at night in mouse brain (23,28,30). So, we tested that whether AHI1 affects TH expression at different times of the day.…”
Section: Decreased Th Expression In Ahi1 Ko Mouse Midbrains and Ahi1 mentioning
confidence: 99%
See 2 more Smart Citations
“…2G). Altogether, behavioral testing revealed reduced depression-and anxiety-like behaviors, increased risk-taking, unusual aggression as well as slower locomotor habituation to novelty in KO mice, which together are considered mania-like behavioral phenotypes in rodents (Chung et al, 2014;Logan and McClung, 2016), modeling traits occurring during the manic phase of Bipolar Disorder (BD).…”
mentioning
confidence: 99%